Coexistence of morphologically similar bats (Vespertilionidae) on Madagascar: stable isotopes reveal fine-grained niche differentiation among cryptic species. (March 2015) - Dammhahn, Melanie; Rakotondramanana, Claude Fabienne; Goodman, Steven M.
Abstract: Based on niche theory, closely related and morphologically similar species are not predicted to coexist due to overlap in resource and habitat use. Local assemblages of bats often contain cryptic taxa, which co-occur despite notable similarities in morphology and ecology. We measured in two different habitat types on Madagascar levels of stable carbon and nitrogen isotopes in hair (n = 103) and faeces (n = 57) of cryptic Vespertilionidae taxa to indirectly examine whether fine-grained trophic niche differentiation explains their coexistence. In the dry deciduous forest (Kirindy), six sympatric species ranged over 6.0‰ in δ15N, i.e. two trophic levels, and 4.2‰ in δ13C with a community mean of 11.3‰ in δ15N and −21.0‰ in δ13C. In the mesic forest (Antsahabe), three sympatric species ranged over one trophic level (δ15N: 2.4‰, δ13C: 1.0‰) with a community mean of 8.0‰ δ15N and −21.7‰ in δ13C. Multivariate analyses and residual permutation of Euclidian distances in δ13C–δ15N bi-plots revealed in both communities distinct stable isotope signatures and species separation for the hair samples among coexisting Vespertilionidae. Intraspecific variation in faecal and hair stable isotopes did not indicate that seasonal migration might relax competition and thereby facilitate the local co-occurrence of sympatric taxa.